Expanded clay aggregates multi-functionality for water purification: Disinfection and adsorption studies. Issue 1 (1st January 2021) - Ihekweme, Gina O.; Obianyo, Ifeyinwa I.; Anosike-Francis, Esther N.; Anyakora, Victoria N.; Odusanya, O. S.; Onwualu, Azikiwe P.
Abstract: Elevated levels of contaminants in surface and ground water pose serious and adverse health challenges in the twenty-first century. It is imperative that the quality of life of people without safe drinking water is improved by providing safe, clean and affordable water using appropriate purification technology. Natural clay and rice husk-Na2 CO3 modified clay were used to produce expanded clay aggregates adsorbents. Characterizations were done using SEM, XRD, XPS and BET to reveal their salient features. Filtration studies were carried out to ascertain the disinfection assay of E. Coli and removal efficiencies of nitrate and phosphate. Batch adsorption experiments were employed to determine the effect of pH, contact time and adsorbent dosage for effective removal of Arsenic (III) and lead (II) including isotherm models. Aluminosilicates and associated minerals with high surface areas between 456.143–566.998 m 2 /g and significant adsorption sites were revealed. Log four bacteria disinfection assay was achieved. Reduction efficiencies for phosphate and nitrate for all adsorbents varied from 27.33% to 76% and 10.67% to 46% respectively. High correlation coefficients made Langmuir isotherm model more favourable than Freundlich model. The adsorption capacities for both lead and arsenic were high and reaction was fast, making the adsorbents suitable for water remediation applications.